Hypertriglyceridemia in Newly Diagnosed Acute Promyelocytic Leukemia - Sun, Jianai; Lou, Yinjun; Zhu, Jingjing; Shen, Huafei; Zhou, De; Zhu, Lixia; Yang, Xiudi; Xie, Mixue; Li, Li; Huang, Xianbo; Zhu, Mingyu; Zheng, Yanlong; et al. (Frontiers in Oncology, 2020)
The primary aim of the present retrospective study was to investigate lipid profiles and kinetics in acute promyelocytic leukemia (APL) patients. We analysed 402 newly diagnosed APL patients and 201 non-APL patients with acute myeloid leukemia (as control). Incidence of hypertriglyceridemia in APL patients and non-APL patients was 55.82% and 28.4% (p = 0.0003). The initial levels of triglycerides, total cholesterol, high-density lipoprotein cholesterol and low-density lipoprotein cholesterol were higher in APL patients than in control (all p < 0.0001). In APL patients triglyceride levels were significantly increased during induction treatment with all-trans retinoic acid and arsenic. Multivariable analysis showed that age, being overweight (body mass index ≥25) and APL were independent risk factors for hypertriglyceridemia in all patients before treatment. High triglyceride levels were not significantly associated with disease-free survival or overall survival in the APL patients. In summary, in the current study triglyceride levels were significantly elevated in APL patients before treatment, and they increased during induction treatment, but there were no significant corresponding effects on survival.